2017
DOI: 10.1055/s-0037-1602132
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes following Single- and Multiple-Radius Total Knee Replacement: A Randomized, Controlled Trial

Abstract: Final accepted manuscriptWhilst single-radius designs of total knee replacement (TKR) have theoretical benefits, the clinical advantage conferred by such designs is unknown. The aim of this randomised, controlled study was to compare the short-term clinical outcomes of the two design rationales. 105 knees were randomised to receive either single radius (Scorpio, Strkyer, Newbury, UK; SR group) or multiple radius (AGC, Biomet, Bridgend, UK; MR group) TKR.Patient reported outcomes (Oxford Knee Score, OKS and Kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…We identified 595 articles initially through both online and manual searches undertaken up to February 2020. After we applied the exclusion criteria, ultimately nine RCTs remained to be analyzed in this meta-analysis [14,[19][20][21][22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 595 articles initially through both online and manual searches undertaken up to February 2020. After we applied the exclusion criteria, ultimately nine RCTs remained to be analyzed in this meta-analysis [14,[19][20][21][22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…These findings correlated with the results of the randomized studies that focused on the postoperative functional outcomes. Mushtaq et al [25] compared 54 patients with MR and 51 with SR and observed no significant differences in KSS and OKS. Moreover, Jo et al [21] compared 50 patients with SR and 50 with MR, and found no significant differences in HSS score, ROM, and WOMAC either.…”
Section: Discussionmentioning
confidence: 99%
“…Patella tilt, patella height, patella thickness, and delta angle were predictors of secondary patella resurfacing when different variants (CR, PS, condylar constrained) of a multiradius patella-friendly TKA design were compared [49]. In an RCT, a single radius was compared to a multiradius design and no differences were found when OKS and KSS scores were used [50]. In a prospective bilateral randomized trial using a single-radius PS, TKA patients were unaware of any differences due to patellar resurfacing as assessed by postoperative anterior knee pain, Forgotten Joint Score, and an objective Feller patellofemoral score at 11-year follow-up [21].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline data of included studies was summarized in Table 1. A total of 13 RCTs 7,17,18,20,23,[26][27][28]33,35,42,44,45 All patients included in these studies suffered from degenerative knee arthritis. The SR knee prosthesis used in included studies comprised Scorpion, Scorpion NRG, Triathlon, and Trekking knee system.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the inclusion of some retrospective studies limits its reliability. In addition, many RCTs have been published from then on, among which the controversy still persists 20 , 21 , 22 , 23 , 25 , 26 . Therefore, it is strongly necessary to update this meta‐analysis only including prospective randomized controlled trials to determine whether there were clinical advantages to SR‐TKA over MR‐TKA.…”
Section: Introductionmentioning
confidence: 99%